PENGEMBANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMAN 1 KUPANG - Tiwuk Widiastuti; Immanuel K P Rini; Meiton Boru (Universitas Nusa Cendana, 2020)
Information System is an activity of organized procedures, which when executed will produce information. Development of academic information systems in SMAN 1 KUPANG because the old system is only limited to web profiles and has not supported teaching and learning activities. This information system is expected to support the educational activities, namely in terms of making it easier for data processing in the presentation of school information.. This study uses the PHP 5.6.30 programming language and HTML for storage using mysql 10.1.21. This study uses two tests, testing the system using WAPT tools and testing the questionnaire with a biverate person. System testing consists of 3 parts, namely performance testing, stress testing and volume testing, the results of testing performance testing 164 percents / s and stress testing between ranges of levels 2 to 31. There are 4 criteria for questionnaire testing to see the success of the system being developed, 4 criteria These are the interface, speed, benefits and ease of the system. The results of questionnaire testing correlated between intertface and ease of 67.6%, interface and system benefits by 58.6% and correlation between interface and system speed by 62.1%.